Experimental study of the efficacy of combined use of cancer vaccine and interferon - Potebnya, G.P.; Kudryavets, Yu.Y.; Lisovenko, G.S.; Cheremshenko, N.L.; Voeykova, I.M.; Trokhimenko, N.V.; Symchich, T.V.; Evstrateyva, L.M. (Experimental Oncology, 2007)
Aim: To study in in vivo model the efficacy of combined scheme of administration of cancer vaccine (CV) and interferon (IFN). Materials and Methods: Lewis lung carcinoma (LLC) was transplanted to male C57Bl mice. For treatment, CV prepared from LLC cells with the use of cytotoxic lectins of B. subtilis B-7025, and preparation of murine IFN-alpha were used. Therapeutic effect was evaluated by measurement of tumor volume and analysis of average life span (ALS) of treated animals. Immunologic study included determination of antitumor cytotoxicity of T-lymphocytes (CTL) and natural killer (NK) cells by radiometric method, functional activity of peritoneal macrophages (MP) — by colorimetric test with nitroazole blue, and evaluation of titers of tumor necrosis factor (TNF) and interleukins-1 and -2 (IL-1, 2). Results: It has been shown that the use of IFN preparation significantly elevated efficacy of vaccine therapy of solid form of LLC: duration of latent period of tumor growth elevated by 25%, ALS — by 28%, index of tumor growth inhibition — by 35–40%. Upon combined use of CV and IFN, significant activation of the cells — effectors of nonspecific immune defense (MP), and specific one (CTL) was observed. Conclusion: The obtained results evidence on perspectiveness of the development of combined schemes of administration of CV and IFN for elevation of the efficacy of vaccine therapy.